1998
DOI: 10.1021/tx9801716
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Mechanism of the Carcinogenic Activation of N-Nitrosodiethanolamine with Deuterium Isotope Effects:  In Vivo Induction of DNA Single-Strand Breaks and Related in Vitro Assays

Abstract: A series of bioassays, including in vivo induction of DNA single-strand breaks (SSB) and cytotoxicity in cytochrome P450 2E1-transfected cells, were utilized with N-nitrosodiethanolamine (NDELA), its deuterated isotopomers (alpha-D4NDELA and beta-D4NDELA), N-nitroso-2-hydroxymorpholine (NHMOR), and two of its deuterated isotopomers (2-D-NHMOR and 5,5-D2-NHMOR) to probe the mechanism of carcinogenic activation of NDELA and the role of its metabolite NHMOR. DNA samples, taken from the livers of male Wistar rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Deuterium isotope effects have been used extensively in the study of the mechanisms of nitrosamine-induced carcinogenesis (18,(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). The first experiment to utilize deuterium substitution in the study of nitrosamineinduced cancer demonstrated that perdeuteration of NDMA lowered the liver carcinogenicity of this compound in rats (65).…”
Section: (4r)-[4-2 H 1 ]Nnk Was Less Tumorigenic Than Nnk and (4s)-[4mentioning
confidence: 99%
“…Deuterium isotope effects have been used extensively in the study of the mechanisms of nitrosamine-induced carcinogenesis (18,(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). The first experiment to utilize deuterium substitution in the study of nitrosamineinduced cancer demonstrated that perdeuteration of NDMA lowered the liver carcinogenicity of this compound in rats (65).…”
Section: (4r)-[4-2 H 1 ]Nnk Was Less Tumorigenic Than Nnk and (4s)-[4mentioning
confidence: 99%
“…Because our deuteration experiments (20) with NDELA in vivo pointed toward an R-hydroxylation pathway for this compound, we reconsidered the applicability of the method shown in Scheme 1 to the detection of glycolaldehyde, a very polar aldehyde, which is also susceptible to osazone reactions with hydrazines to give hydrazones of glyoxal. Isooctane is a very nonpolar organic solvent, and the possibility that it would not extract either the DNP of glycolaldehyde or glyoxal was considered prior to the initiation of the work presented here.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were grown at 37°C in a humidified atmosphere containing 5% CO 2 . References for enzymes primarily involved in metabolic activation: [13][14][15] 4 Methylhydroxylation activity of tolbutamide. 5 4' -Hydroxylation activity of S-mephenytoin.…”
Section: Introductionmentioning
confidence: 99%